pCO(2) and pH regulation of cerebral blood flow - Yoon, SeongHun (Frontiers Media S.A., 2012)
CO(2) serves as one of the fundamental regulators of cerebral blood flow (CBF). It is widely considered that this regulation occurs through pCO(2)-driven changes in pH of the cerebral spinal fluid (CSF), with elevated and lowered pH causing direct relaxation and contraction of the smooth muscle, respectively. However, some findings also suggest that pCO(2) acts independently of and/or in conjunction with altered pH. This action may be due to a direct effect of CSF pCO(2) on the smooth muscle as well as on the endothelium, nerves, and astrocytes. Findings may also point to an action of arterial pCO(2) on the endothelium to regulate smooth muscle contractility. Thus, the effects of pH and pCO(2) may be influenced by the absence/presence of different cell types in the various experimental preparations. Results may also be influenced by experimental parameters including myogenic tone as well as solutions containing significantly altered HCO(3)(−) concentrations, i.e., solutions routinely employed to differentiate the effects of pH from pCO(2). In sum, it appears that pCO(2), independently and in conjunction with pH, may regulate CBF.